3D culture platform of human iPSCs-derived nociceptors for peripheral nerve modeling and tissue innervation. (30th November 2021) - Malheiro, Afonso; Harichandan, Abhishek; Bernardi, Joyce; Seijas-Gamardo, Adrián; Konings, Gonda F; Volders, Paul G A; Romano, Andrea; Mota, Carlos; Wieringa, Paul; Moroni, Lorenzo
Abstract: Functional humanized in vitro nerve models are coveted as an alternative to animal models due to their ease of access, lower cost, clinical relevance and no need for recurrent animal sacrifice. To this end, we developed a sensory nerve model using induced pluripotent stem cells-derived nociceptors that are electrically active and exhibit a functional response to noxious stimuli. The differentiated neurons were co-cultured with primary Schwann cells on an aligned microfibrous scaffold to produce biomimetic peripheral nerve tissue. Compared to glass coverslips, our scaffold enhances tissue development and stabilization. Using this model, we demonstrate that myelin damage can be induced from hyperglycemia exposure (glucose at 45 mM) and mitigated by epalrestat (1 µ M) supplementation. Through fibrin embedding of the platform, we were able to create 3D anisotropic myelinated tissue, reaching over 6.5 mm in length. Finally, as a proof-of-concept, we incorporated pancreatic pseudoislets and endometrial organoids into our nerve platform, to demonstrate the potential in generating nociceptor innervation models. In summary, we propose here an improved tool for neurobiology research with potential applications in pathology modeling, drug screening and target tissue innervation.